2013
DOI: 10.1371/journal.pone.0081418
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence That Anodal Transcranial Direct Current Stimulation Enhances Time to Task Failure of a Sustained Submaximal Contraction

Abstract: The purpose of this study was to determine whether anodal transcranial direct current stimulation (tDCS) delivered while performing a sustained submaximal contraction would increase time to task failure (TTF) compared to sham stimulation. Healthy volunteers (n = 18) performed two fatiguing contractions at 20% of maximum strength with the elbow flexors on separate occasions. During fatigue task performance, either anodal or sham stimulation was delivered to the motor cortex for up to 20 minutes. Transcranial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
160
5
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(185 citation statements)
references
References 67 publications
5
160
5
15
Order By: Relevance
“…We cannot infer, on the basis of our results, whether this facilitatory effect was due mainly to the enhancing of motivation and/or descending drive to the motorneuron pool. The finding that anodal tDCS prolonged the contraction time of the suprahyoid/submental muscles agrees with evidence that anodal tDCS may prolong the duration of muscle contraction during a high degree of effort [34,35]. Moreover, it could indicate the involvement of cortical areas responsible for motor planning.…”
Section: Discussionsupporting
confidence: 86%
“…We cannot infer, on the basis of our results, whether this facilitatory effect was due mainly to the enhancing of motivation and/or descending drive to the motorneuron pool. The finding that anodal tDCS prolonged the contraction time of the suprahyoid/submental muscles agrees with evidence that anodal tDCS may prolong the duration of muscle contraction during a high degree of effort [34,35]. Moreover, it could indicate the involvement of cortical areas responsible for motor planning.…”
Section: Discussionsupporting
confidence: 86%
“…However, 80% of the participants had poorer performance post-stimulation in comparison to baseline on the c-tDCS condition. There have been a few studies that have not found significant effects of motor cortex c-tDCS on strength-related measures (8,45,46). In contrast, there is also evidence suggesting that c-tDCS on the hand motor cortex can induce prolonged excitability decreases, reducing the amplitude of transcranial magnetic stimulation suggested that c-tDCS on the motor cortex can actually induce long-lasting after-effects not only in intracortical networks but also in cortico-motorneuronal axons below the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…At neurophysiological level, tDCS placing anode electrode placed over M1 with the current intensity of 1.5 mA increases MEP amplitude in young (Karok and Witney 2013, Tremblay et al 2013a, Williams et al 2013) and older adults (Puri et al 2016, Puri et al 2015.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 96%